PERCEIVED SOCIO-CULTURAL IMPACTS OF CHILDLESSNESS ON MARRIED COUPLES IN ZARIA LGA OF KADUNA STATE, NIGERIA - Saliu, Hauwa; Abubakar, Maryam; Ojumu, Charles Ali (African Journal of Social and Behavioural Sciences, 2024)
This study assesses the perceived socio-cultural impact of childlessness among married couples in Zaria LGA of Kaduna State, Nigeria. The study explores public perception of the causes of childlessness among married couples; sociocultural implications resulting from childlessness on married couples and contributions of family members towards mitigating the impact of childlessness on married couples. This Descriptive study engages 400 respondents through the use of a multi-stage cluster sampling method. The study found that childlessness is considered to be a medical problem, as such identified low sperm count (male), ovulation factor (abnormal menses for females), damaged uterus (female), fibroid (female), and STDs (both male and female) as the significant medical problems attributed to childlessness. The study also revealed that as a result of childlessness, the husband’s mother mostly compels the husband to take another wife. The relationship between the wife/husband and their in-laws is strained. On the contributions of family members towards mitigating the impact of childlessness on married couples, findings show that the wife’s relatives and her friends play positive roles. The study recommends a need for community education and awareness implemented through community-wide educational programs, especially for newly wedded couples emphasizing the medical aspects. In-laws and relatives from both sides should have shared feelings of empathy and concern for both couples and explore alternative strategies collectively towards ameliorating the problem rather than attributing blame to either of the couples that might lead to a strained relationship.